2014
DOI: 10.4236/ojped.2014.44036
|View full text |Cite
|
Sign up to set email alerts
|

Fever among Children with Sickle-Cell Disease: Findings from the General Pediatric Ward of the Owendo Pediatric Hospital in Libreville, Gabon

Abstract: Sickle-cell disease (SCD) represents a substantial public health problem in Gabon. Fever is one of the principal reasons for the hospitalization of children afflicted by major sickle-cell disorder, since it can be a clinical reflection of severe infections that have the potential to become life threatening. Objectives: Identification of the main causes of fever in children with SCD in our clinical setting, with the aim of optimizing treatments. Patients and Methods: This is a retrospective study of all the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…For the population studied in this cohort, there seems to be an indication for the use of a broad spectrum cephalosporin in combination with either a macrolide or quinolone for empiric coverage of febrile patients. Incidence of acute osteomyelitis, meningitis, or acute cholecystitis were lower than those reported by Williams in Kenya [34], Akar in Kowet [35], Mava in Nigeria [36], and Koko in Gabon [37]. This difference can be explained by a difference in immunization status between our population and those studied by others.…”
Section: Discussioncontrasting
confidence: 79%
“…For the population studied in this cohort, there seems to be an indication for the use of a broad spectrum cephalosporin in combination with either a macrolide or quinolone for empiric coverage of febrile patients. Incidence of acute osteomyelitis, meningitis, or acute cholecystitis were lower than those reported by Williams in Kenya [34], Akar in Kowet [35], Mava in Nigeria [36], and Koko in Gabon [37]. This difference can be explained by a difference in immunization status between our population and those studied by others.…”
Section: Discussioncontrasting
confidence: 79%
“…[8]. In this Gabonese study, it was reported that fever was associated with plasma infection in 43.5% and 55.25% of cases of fever without known etiologies [56,64]. An association of bacteremia with low hemoglobin levels was revealed in a study in Tanzania.…”
Section: Sickle Cell Anemia and Invasive Bacteremias Or Infectionsmentioning
confidence: 81%
“…A genetic hematological disorder, SCD affects 7% of the global population and 4.2% of Saudi Arabia’s population [ 2 , 3 ]. Fever is a significant condition in children with SCD, often indicating serious underlying conditions requiring medical attention [ 4 ]. SCD children face an increased risk of invasive infection, morbidity, and mortality due to splenic dysfunction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%